Pasar Nongkrong Modern - Richard Juan Austen; Agustinus Sutanto (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2020)
The Special Capital Region of Jakarta (DKI Jakarta) is the country's capital and largest city in Indonesia. Jakarta as a large capital city has an attraction as a place to look for income, it is very attractive for residents from various regions in Indonesia to come to Jakarta who are settled and claim to be citizens of Jakarta. The number of migrants in Jakarta is around 68,500 people and it is predicted that as many as 60% live in Jakarta. Jakarta is a city with a fairly rapid economic growth rate. At present, more than 70% of state money is circulating in Jakarta. Since the early 1980s, the DKI Jakarta Government has been intensively building modern shopping centers, or commonly known as malls and plazas. At present Jakarta is one of the cities in Asia that has many shopping centers. In addition to luxury shopping centers, Jakarta also has many traditional markets and wholesale trade centers. For smaller environments, shopping centers for daily necessities are also available at affordable prices, such as Indomaret and Alfamart. The city of Jakarta as the capital of Indonesia focuses its development as the center of Indonesian business so that it is now densely filled with houses and tall buildings. The condition of the city of Jakarta is dense with residents and buildings, certainly there are many problems that arise, and the main problems of the city of Jakarta such as traffic jams, social problems and flooding. Traffic congestion makes Jakarta residents become lazy to leave the house so that an individualistic lifestyle makes social interaction decrease, also causes stress. The lives of Jakarta residents who live in high-rise buildings such as apartments that are mushrooming in Jakarta, which are very individual and cannot interact with the surrounding environment and daily activities are only "confined" in apartment units create a boring atmosphere and make residents become stressed. The problems faced by the City of Jakarta, of course, require solutions that really must be considered by the Government, especially the Local Government of the City of Jakarta. For that reason the author tries to make a city facility that can be a bridge between activities at home and work activities, in the social and economic fields in the form of Third Place, named Modern Hangout Market. Abstrak Daerah Khusus Ibukota Jakarta ( DKI Jakarta ) adalah ibu kota negara dan kota terbesar di Indonesia. Jakarta sebagai ibu kota yang besar memiliki daya tarik sebagai tempat untuk mencari penghasilan, sangat memikat penduduk dari berbagai daerah di Indonesia untuk datang ke Jakarta yang menetap dan mengaku sebagai warga Jakarta. Jumlah warga pendatang di Jakarta sekitar 68.500 orang dan diprediksi sebanyak 60% tinggal di Jakarta. Jakarta merupakan kota dengan tingkat pertumbuhan ekonomi yang cukup pesat. Saat ini, lebih dari 70% uang negara beredar di Jakarta. Sejak awal tahun 1980, Pemerintah DKI Jakarta gencar membangun pusat-pusat perbelanjaan modern, atau biasa yang dikenal dengan mall dan plaza. Saat ini Jakarta merupakan salah satu kota di Asia yang banyak memiliki pusat perbelanjaan. Di samping pusat-pusat perbelanjaan mewah, Jakarta juga memiliki banyak pasar-pasar tradisional dan pusat perdagangan grosir. Untuk lingkungan yang lebih kecil, tersedia pula pusat belanja kebutuhan sehari-hari dengan harga yang terjangkau, seperti Indomaret dan Alfamart. Kota Jakarta sebagai ibukota dari Indonesia memfokuskan perkembangannya sebagai pusat perbisnisan Indonesia sehingga kini telah padat dipenuhi hunian dan bangunan tinggi. Kondisi kota Jakarta yang padat dengan penduduk dan bangunan, pasti banyak permasalahan yang muncul, dan yang menjadi permasalahan utama kota Jakarta seperti kemacetan lalu lintas, permasalahan sosial dan banjir. Kemacetan lalu lintas membuat warga Jakarta menjadi malas untuk keluar rumah sehingga gaya hidup yang individualistik membuat menurunnya interaksi sosial, juga menjadi penyebab stress. Kehidupan warga Jakarta yang tinggal di gedung-gedung bertingkat tinggi seperti Apartemen yang menjamur di Jakarta, yang sangat individual dan tidak bisa berinteraksi dengan lingkungan sekitar dan aktifitas sehari-hari hanya “terkurung” dalam unit apartemen membuat suasana yang membosankan dan bikin penghuninya menjadi stress. Permasalahan yang dihadapi oleh Kota Jakarta, tentunya membutuhkan pemecahan yang benar-benar harus dipikirkan oleh Pemerintah, khususnya Pemerintah Daerah Kota Istimewa Jakarta. Untuk itu Penulis mencoba membuat suatu  fasilitas kota yang bisa sebagai jembatan penghubung antara kegiatan di rumah dan aktifitas kerja, dalam bidang sosial dan ekonomi berupa Third Place yang diberi nama Pasar Nongkrong Modern.